Direct-writing of 3D periodic TiO2 bio-ceramic scaffolds with a sol-gel ink for in vitro cell growth. (15th April 2018) - Wang, Rong; Zhu, Pengfei; Yang, Weiyi; Gao, Shuang; Li, Bo; Li, Qi
Abstract: In this work, three-dimensional (3D) periodic TiO2 bio-ceramic scaffolds were created by continuous filament writing with TiO2 sol-gel ink followed by sintering. The TiO2 sol-gel ink has the advantage of creating 3D bio-ceramic scaffolds with finer feature size than commonly used ceramic powder based ink systems. The structure, pore sizes, and interconnectivity could be controlled through 3D structure design and printing parameter adjustment. To evaluate the potential of these 3D TiO2 bio-ceramic scaffolds for bone tissue engineering, the mouse osteoblastic cell line MC3T3-E1 was cultured on them. The observed good viability demonstrated that 3D TiO2 bio-ceramic scaffolds created by direct-writing technique provide a biocompatible environment that favors cell growth and attachment. Graphical abstract: Highlights: Continuous filament writing with a sol-gel ink enables finer feature size than ceramic powder-based ink systems. Their structure and pore size/interconnectivity could be well controlled compared with uncontrollable porous TiO2 foams. Culturing of mouse osteoblastic cell line MC3T3-E1 shows that 3D TiO2 bio-ceramic scaffolds favor cell growth and attachment.